INSENTIF BERPENGARUH TERHADAP KINERJA PADA KARYAWAN PT. ATEJA TRITUNGGAL DI KABUPATEN BANDUNG BARAT - Muriawan, R. Suyudi (JURISMA : Jurnal Riset Bisnis & Manajemen, 2017)
This study titled: incentives affect the performance of employees of PT. Ateja Tritunggal in West Bandung regency. Initial research indicates that in recent years there has been a decrease in performance related to the incentives given to employee companies. The purpose of this study is to find out how much incentives affect the performance of employees of PT. Ateja Tritunggal in West Bandung regency. The method of this research is descriptive and associative research, with data coming from responses 85 respondents. Data analysis used with simple linear regression analysis. The result of descriptive analysis shows that Incentives and Performance have good average value based on standard weight classification. Associated with the existing phenomenon of this condition still needs to be improved again so as to achieve a very good condition, while the influence of incentives to employee performance of 68.90%. This is because incentives are motivation or encouragement that is needed by employees means that the better the incentive will be able to improve the performance of employees of PT. Ateja Tritunggal in West Bandung regency. Keywords: Incentives, Performance, Employees